Gender Sensitive Teaching at Don Honorio Ventura Technological State University: Basis for Enhancement of Gender and Development (GAD) Programs - Gamboa, Jerame; Gamboa, Alberto; Mendoza, Grace; Tesoro, Elena (Technium Social Sciences Journal, 2020)
The study was done to describe the gender sensitive teaching at Don Honorio Ventura Technological State University (DHVTSU) as a basis for the enhancement of the Gender and Development Program. Descriptive research was employed. The Deans, faculty members, and students of the university answered the questionnaire and interview as guided by various GAD Handbooks. Gender sensitive teaching is commonly noted as equality. Moreover, gender sensitive teaching was fully applied and fully observed in the areas of curriculum, learning objectives, learning content, learning experiences, textual materials, and learning assessment. However, issues on integration and proper application of gender sensitive teaching was raised among technical, technology, sciences, and mathematical courses With such conditions, continuous monitoring and trainings should be done so that the full application and full observance of gender sensitive teaching can be sustained. Also, a creation of module on how to concretely become gender neuter in all aspects of the educative process should be initiated.